Medical management of invasive fungal infections of the central nervous system in pediatric cancer patients. Issue 6 (18th November 2014) - Carter, John H.; Lenahan, Jennifer L.; Ishak, Gisele E.; Geyer, J. Russell; Pollard, Jessica; Englund, Janet A.
<x xml:space="preserve">Abstract</x> Fungal infections of the central nervous system (CNS) are associated with high mortality rates in immunocompromised patients. Surgical intervention is a mainstay of therapy, but not always possible. We describe the use of medical therapy for the treatment of CNS fungal infections in four pediatric cancer patients. Definitive resection was not performed in any patient. All patients initially received combination antifungal therapy with good clinical response; long‐term survival was documented in two patients able to transition to long‐term azole therapy. Prolonged antifungal therapy is an important option for treating invasive CNS fungal infections when surgery is not feasible. Pediatr Blood Cancer 2015;62:1095–1098. © 2014 Wiley Periodicals, Inc.